Somewhere Out There May Be That Life-Saving Research - Paz-Pacheco, Elizabeth (Journal of the ASEAN Federation of Endocrine Societies, 2014)
We are happy to report that JAFES, after being listed in the Directory of Open Access Journals (DOAJ), is now included in the Research 4 Life (R4L) of the Health InterNetwork Access to Research Initiative (HINARI), a program under the World Health Organization. HINARI provides free or very low cost online access to biomedical/social science journals to benefit not-for-profit institutions in developing countries. JAFES is now among the publishers providing free access to its articles to those who have limited financial capability. We believe that the benefits of scientific knowledge should be for everyone, free to build upon, readily available to generate further understanding of endocrine and metabolic conditions that are steadily increasing in prevalence worldwide.